PERANAN PENYIDIK POLRI DALAM MELAKUKAN PENYIDIKAN TINDAK PIDANA MELANGGAR UNDANG – UNDANG NO. 35 TAHUN 2009 TENTANG NARKOTIKA DI POLRESTA SAMARINDA - Handika Pratama Lestari (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT In the investigation of criminal offenses drugs, then that act is part detective dealing with narcotics in this regard narcotics unit. The division of tasks of this kind there are in each Regional Police in Indonesia. Action investigations conducted by the Police is the first process of the criminal proceedings. Investigation in principle aims to find and collect evidence, that the evidence it sought to make light of criminal acts that occur and to find the suspect. Steps or techniques of investigation of criminal drug include: Observation; Surveillance (stalking); Undercover Agent (Infiltration Agent); Purchasing Covert (undercover buy); Controlled Drug Submission (Controlled Dellivery); Raid Planning Execution (Execution Plan raids). The obstacles faced by investigators in performing their duties, among others: In conducting criminal investigations of drugs, barriers exist in terms of personnel in Samarinda Police are barriers of lack of special education obtained. In the investigation of drug cases should be minimal investigators never get educated about the investigation of drug cases. Lack of public knowledge about the characteristics of the drug. Drugs as a material that should always be supervised because of the hazardous nature, the drug should be known by the community characteristics. Society needs mengetahi the characteristics of narcotic plants in order to prevent the perpetration of the crime of drug. Until now, the community can be said about knowing the characteristics of the drug, there should be efforts to disseminate information about the characteristics of drugs.